Study on the epistemological foundations of the administration - Espinoza Herrera, Nemesio (2018)
Epistemology is directly linked to Science, Scientific Research, Administration and Philosophy. In highly professional universities of our society, where the production of Science and Technology through Scientific Research, is not necessarily a priority mission, epistemology is still unconnected with university work, which results there are no sustained studies on it and its concepts, as a rule, are still ambiguous and distorted.The societies of the new century and millennium need a new university understood as an eminently center of production of Science and Technology through Scientific Research, and on that basis, forming a new type of competent professionals for development. This new university requires new approaches on epistemology to promote Scientific Research, Science Teaching, Science-based Administration and Philosophy.